Initial clinical scans using [18F]ACI‐12589, a novel α‐synuclein PET‐tracer. (20th December 2022) - Smith, Ruben; Capotosti, Francesca; Schain, Martin; Ohlsson, Tomas; Touilloux, Tanja; Hliva, Valerie; Vokali, Efthymia; Luthi‐Carter, Ruth; Molette, Jerome; Dimitrakopoulos, Ioannis K; Jögi, Jonas; Stomrud, Erik; et al.
Abstract: Background: To study the ability of the newly developed α‐synuclein Positron Emission Tomography (PET) tracer, [ 18 F]ACI‐12589, created and developed by AC Immune SA, to detect α‐synuclein neuropathology in vivo, in clinically diagnosed patients with α‐synucleinopathies. Method: We intend to scan a total of up to 50 participants with different diseases associated with α‐synuclein and age‐ and gender‐matched controls. These will include participants with Parkinson's disease (PD), Multiple System Atrophy (MSA), Dementia with Lewy bodies (DLB), or Parkinson's disease caused by a duplication in the α‐synuclein gene, in addition to neurologically healthy volunteers. At the time of abstract submission, 23 participants have undergone [ 18 F]ACI‐12589 PET scans. 20 scans consist of 0‐90 min dynamic scans with arterial blood sampling for blood input activity and metabolite analysis, two are full dynamic scans and one a 60‐90 min static scan without blood sampling. In addition, participants have undergone structural MRI, DaTscan or [ 18 F]DOPA PET, and cognitive and motor testing (UPDRS‐III). Result: The data are currently being processed and analyzed. Initial image analyses suggest that there is ACI‐12589 retention in brain areas affected by the disease process (such as the basal ganglia and cerebellar white matter) in participants with MSA, but also a potential age‐dependent retention in the basal ganglia and brain stem of controls. Conclusion: We will be presenting initial promising clinical data on the novel α‐synuclein PET tracer [ 18 F]ACI‐12589, the initial analysis of which suggests tracer binding consistent with expected patterns of α‐synuclein pathology based on clinical manifestations. Further analyses are ongoing and our updated findings will be presented at the conference.